Research and Analysis on the Cultivation of Intelligent Transportation Technology Professionals under the Background of Integration of Production and Education - Ying Zhang; Yongxiang Zhu (International Transactions on Electrical Energy Systems)
In order to improve the training effect of transportation technology professionals, this paper combines the intelligent digital signal processing method to process the data of the integration of production and education, and explores the training process of transportation technology professionals. In the process of data processing of industry-education fusion, this paper demodulates the nuclear magnetic resonance signal obtained after A/D conversion from the carrier frequency signal and places it at zero frequency. At the same time, this paper realizes the separation of the real part and the imaginary part of the nuclear magnetic resonance signal and constructs the digital sine table and digital cosine table of the carrier reference frequency. In addition, the data output by the ADC is subjected to quadrature detection to become two data signals, which are the in-phase component and the quadrature component. Finally, this paper constructs an intelligent analysis model. The simulation results show that the talent training method of intelligent transportation technology based on the integration of production and education has good effects, which can effectively improve the training effect of transportation technology professionals.